Pemanfaatan Game Interaktif Wordwall untuk Meningkatkan Hasil Belajar Peserta Didik Kelas V pada Mata Pelajaran Matematika di SD Negeri 22 Pekanbaru - Rahma Sari, Gusnia; Andesti, Mutia; Suci Amelia, Putri; Kurniaman, Otang; Noviani, Jumraul (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to improve mathematics learning outcomes of grade V students at SD Negeri 22 Pekanbaru by using learning media, namely the Wordwall interactive game. This study used the method of Classroom Action Research (PTK) with Kemmis and McTaggart design consisting of two cycles, each including planning, implementation, observation, and reflection. The object of this study was 16 fifth grade students. Data collection was carried out through observation, testing, and documentation, then analyzed by the percentage of learning completeness using the Minimum Completeness Criteria (KKM) of 75. The results showed a significant increase in student learning outcomes from cycle I to cycle II, with the percentage of learning completeness increasing from 56% to 81%. The average score of learning outcomes also increased from 73.5 in cycle I to 86.2 in cycle II. This increase was due to the use of Wordwall which made math learning more interesting, interactive, and fun, and was supported by the provision of printed teaching materials in cycle II. This study found that Wordwall learning media can increase the motivation, engagement, and learning outcomes of fifth grade math students. It is suggested that future research can develop the use of Wordwall with more varied features and integration with other learning platforms to expand the reach and flexibility of learning.